Jurisdictional Problems to E- Commerce Entity in Online Dispute Resolution - Shobhit Agrawal (International journal of economic perspectives, 2022)
O nline Dispute Resolution (hereinafter ‘ODR’) is well recognized mechanism in resolving disputes now-a-days. In simple words ODR means the resolving of dispute between the disputed parties on internet and physical presence of parties, documents, etc. is not in need. The parties to the disputes are opting ODR more in comparison to the traditional Alternative Dispute Resolution (ADR) and this is because ODR provides more benefits to them. Every process is having their own pros and cons but what matters is that how to overcome those negative aspects to make that process better from other. The basic objective of my research is to scrutinize the reasons to opt ODR over the ADR; the legal concerns that the disputed parties face while opting ODR; and the focus is on the jurisdictional issue which the disputed parties usually face in the ODR, and lastly to propose the possible solutions to overcome the issue of jurisdiction in ODR.